Wireless indoor localization technology based on fingerprint algorithm - Mengdan ZHANG; Guangyue LU; Honggang WANG; Jiming LIU (Dianxin kexue)
As people's demand for location based service（LBS）is increasing, indoor localization has gradually becomes a hot research topic in the field of user location. And the fingerprint orientation is very much popular among most of the researchers, not only because it has high positioning accuracy and strong universality, but also because it doesn't need additional equipment. Firstly, the positioning principle of various kinds of main stream indoor location fingerprint positioning technology was summarized. Then the principle of the existing indoor localization algorithm and its developing condition at present were summarized. Finally, by setting up buildings channel test scenes, all kinds of typical indoor localization algorithm are testified, validated, compared and analyzed. The reference was provided for researchers and people who is researching on indoor location technology.